2013
DOI: 10.1021/ma4013175
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Trends in Precise Acid- and Ion-Containing Polyethylenes at Elevated Temperature

Abstract: The morphologies at elevated temperatures (T > T g , T m ) of 12 precise, polyethylene (PE)-based copolymers with acrylic acid (AA), phosphonic acid (PA), and 1methylimidazolium bromide (ImBr) groups were studied via X-ray scattering. These precise copolymers enable direct comparisons focusing on the length of the spacer between the functional groups and the type of functional group. The polar groups in these materials self-assemble into microphaseseparated aggregates dispersed throughout the nonpolar PE matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 31 publications
6
63
0
Order By: Relevance
“…X‐ray scattering was performed at the multiangle X‐ray scattering (MAXS) facility at the University of Pennsylvania. Details of the MAXS facility can be found in Buitrago et al Data reduction and analysis were performed using the Datasqueeze software . X‐ray scattering profiles were rescaled such that all intensities were equal at q = 10.0 nm −1 , where no peaks are present, so that peak intensities could be compared.…”
Section: Methodsmentioning
confidence: 99%
“…X‐ray scattering was performed at the multiangle X‐ray scattering (MAXS) facility at the University of Pennsylvania. Details of the MAXS facility can be found in Buitrago et al Data reduction and analysis were performed using the Datasqueeze software . X‐ray scattering profiles were rescaled such that all intensities were equal at q = 10.0 nm −1 , where no peaks are present, so that peak intensities could be compared.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The idea of incorporating ions into a polymer structure was applied for different polymers such as polyisobutylene, 4 polystyrenes, 5 or polyethylenes. 6 A large variety of ions were investigated such as sodium cations, 7 quaternary ammoniums 8 and phosphoniums. 9 However, by bearing these ions in their structures, ion-containing polymers exhibit other advantages besides the changes in the rheological and mechanical properties: they are good conductors, selective carriers, antistatic, and antimicrobial materials.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the folding behavior of polyethylene‐like polymers can be controlled by placing bulky substituents at periodically along the polymer backbone, which served as a folding controller . Similarly, research groups of Wagener, Winey, Mecking, and others studied folding of polyethylene‐like chains by periodic placement of hexyl, oligoethylene glycol, sulfonate or even chloro‐ substituents, along the backbone . They also demonstrated the profound effect of periodicity of the substituent on the folding behavior and the lamellar dimensions; in case of randomly distributed branch points, the polymers were found to exhibit curved and segmented morphologies .…”
Section: Introductionmentioning
confidence: 96%